Load Research of Low-Floor Vehicles Bogie Frame Based on VDV 152—2016 - Zhou HE; Pingbo WU; Chaotao LIU; Ye SONG (机车电传动)
The recommendation VDV 152—2016 was introduced, which was the latest one about the strength design on the urban rail vehicles. Besides, the similarities and differences of the strength loads between the new recommendation and the standard EN 13749 were pointed. For a 100% low-floor trailer bogie frame, based on VDV 152—2016, the simulating calculation of both static strength and fatigue strength load cases was worked out by using the finite element analysis method. The results indicated that, for the static strength and fatigue strength the low-floor vehicles bogies frame meets the safety requirements of VDV 152—2016.